(untitled) (Tạp chí Y học Cộng đồng, 2022)
Objectives: To describe surgical characteristics of stage I-IIA non-small cell lung cancer. Subjects and methods: An uncontrolled intervention study on 83 patients diagnosed with stage I - IIa non-small cell lung cancer who underwent thoracoscopy at Military Hospital 175 from January 2015 to December 2020. Results: The average surgical time in the study was 137.5 minutes and the blood loss was not much. Small incisions have an average length of 2.95cm, high aesthetics and low postoperative pain (5.92 days). The patient had a tumor that pulled the visceral pleura 62/83 (74.7%); 21/83 (25.3%) patients with tumors located in parenchyma; 6/83 (7.2%) patients had lung adhesions to the chest wall. There were 2 (2.4%) patients with bleeding complications that required conversion to open surgery; After surgery, there were 7 complications including 1 (1.2%) pneumonia; 1 (1.2%) empyema caused by green pus bacilli; 5 (6.0%) cases of gas leak lasting more than 7 days. Conclusion: Tumor characteristics in surgery include features of tugging visceral pleura, tumor located in parenchyma, lung sticking to chest wall. Common complications include bleeding. Complications after surgery include pneumonia, empyema caused by green pus bacilli, prolonged gas.